CACUL1 functions as a negative regulator of androgen receptor in prostate cancer cells. Issue 2 (1st July 2016) - Choi, Hanbyeul; Lee, Sang Hyup; Um, Soo-Jong; Kim, Eun-Joo
Abstract: The androgen receptor (AR) plays a critical role in the initiation and progression of prostate cancer (PCa), and thus its regulation is an important tool in PCa therapy. Here, we report that CDK2-associated cullin 1 (CACUL1) directly associates with AR and suppresses AR transcriptional activity. In addition, CACUL1 represses histone demethylase LSD1-mediated AR transactivation by competing with LSD1 for AR binding. Depletion of CACUL1 enhances the LSD1 occupancy of the AR-target promoter, accompanied by decreased accumulation of H3K9me2, a repressive transcriptional marker. CACUL1 and LSD1 oppositely regulate CDX-induced cell death in AR-positive LNCaP and metastatic castrate-resistant LNCaP-LN3 cells. These data suggest that CACUL1 impairs LSD1-mediated activation of AR, thereby implicating it as a potential antitumor target in PCa.